PERANCANGAN IT BALANCED SCORECARD DI PERGURUAN TINGGI - Ilahiyah, Mar’a Elthaf; Palupi, Dian (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
The implementation of the MEA competition in the field of higher education is undeniably very closely related to the industrial revolution 4.0 where all teaching and learning process systems no longer use traditional systems but require the practice of using advanced IT technology (Information Technology). The study took the object of the UNISLA private university in Lamongan, emphasizing a qualitative case study approach to see how the implementation of IT components became a Balanced scorecard strategy at UNISLA. There are several strategic goals in implementing the IT balanced scorecard at UNISLA, among others (financial perspective: cost efficiency and profit oriented, customer perspective: increasing the satisfaction of UNISLA users including students, lecturers, and education staff, internal business perspective: developing the use of IT as a the main foundation in UNISLA business processes, learning and growth perspectives: evaluation of IT improvement in UNISLA and improvement of UNISLA users' skills.) From the explanation above we can conclude that why the application of IT in the Balanced Scorecard is so important to be applied as a support in the industrial revolution 4.0.